2021
DOI: 10.3389/fcell.2020.607764
|View full text |Cite
|
Sign up to set email alerts
|

Subchondral Bone Remodeling: A Therapeutic Target for Osteoarthritis

Abstract: There is emerging awareness that subchondral bone remodeling plays an important role in the development of osteoarthritis (OA). This review presents recent investigations on the cellular and molecular mechanism of subchondral bone remodeling, and summarizes the current interventions and potential therapeutic targets related to OA subchondral bone remodeling. The first part of this review covers key cells and molecular mediators involved in subchondral bone remodeling (osteoclasts, osteoblasts, osteocytes, bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 164 publications
2
72
0
Order By: Relevance
“…In a study, it was observed that the phenotype of subchondral trabecular bone beneath healthy cartilage was identical to that of severely injured cartilage, implying that subchondral bone changes in early OA could precede cartilage degradation. 9 Uptake of [18F] NaF indicates remodelling as well as bone metabolism, and is correlated with mineral apposition rate measured by bone histomorphometry. Early OA has been linked to alterations in remodelling of subchondral bone as well as vascularisation; as subchondral bone is metabolically active.…”
Section: Discussion-mentioning
confidence: 99%
“…In a study, it was observed that the phenotype of subchondral trabecular bone beneath healthy cartilage was identical to that of severely injured cartilage, implying that subchondral bone changes in early OA could precede cartilage degradation. 9 Uptake of [18F] NaF indicates remodelling as well as bone metabolism, and is correlated with mineral apposition rate measured by bone histomorphometry. Early OA has been linked to alterations in remodelling of subchondral bone as well as vascularisation; as subchondral bone is metabolically active.…”
Section: Discussion-mentioning
confidence: 99%
“… 88 , 89 Subchondral bone also undergoes remarkable alterations in both composition and structural organization, leading to adverse effects on the overlying articular cartilage. 90 Therefore, targeting the pathways that modify subchondral bone turnover is an attractive option for DMOAD research. 89 The pharmaceutical drugs in phase 2 and 3 stages of development for bone-driven endotype are summarized in Table 2 .…”
Section: Bone-driven Endotypementioning
confidence: 99%
“…In OA joints, subchondral bone undergoes remarkable remodeling processes in both composition and structure, including microarchitecture damage, bone marrow lesions, and bone cysts ( Hu et al, 2021 ). Subchondral bone remodeling is an adaptive change to local biomechanical and biological signals, which correspond to Wolff’s Law ( Zhu et al, 2020 ). When the bone is subjected to abnormal load-bearing, a number of bone properties change, including the increased bone mass, subchondral bone thickening, and trabecular restructuring ( Zhu et al, 2020 ).…”
Section: Cartilage and Oamentioning
confidence: 99%
“…Subchondral bone remodeling is an adaptive change to local biomechanical and biological signals, which correspond to Wolff’s Law ( Zhu et al, 2020 ). When the bone is subjected to abnormal load-bearing, a number of bone properties change, including the increased bone mass, subchondral bone thickening, and trabecular restructuring ( Zhu et al, 2020 ). These alterations are mediated by various types of cells, such as osteoblasts, osteoclasts, and osteocytes ( Sims and Martin, 2020 ).…”
Section: Cartilage and Oamentioning
confidence: 99%